PENGARUH FREE CASH FLOW, EMPLOYEE DIFF, RISIKO LITIGASI DAN KEPEMILIKAN MANAJERIAL TERHADAP MANAJEMEN LABA - Irna Putri Ningtyas; Fatchan Achyani (ITB AAS Indonesia Surakarta, 2025)
This study analyzes the effect of free cash flow, employee diff, litigation risk and managerial ownership on earnings management in food and beverage sector companies listed on the Indonesia Stock Exchange for the period 2019-2023. The sampling technique used in this study was purposive sampling, with a sample size of 22 companies that met the criteria as observation units. The analysis method used was multiple linear regression analysis, and all data had met the classical assumption test. The results showed that the free cash flow variable had an effect on earnings management. Meanwhile, employee diff, litigation risk and managerial ownership did not have an effect on earnings management. Keywords: free cash flow, employee diff, litigation risk, managerial ownership, earnings management